Linarine inhibits inflammatory responses in dry eye disease mice by modulating purinergic receptors - Liu, Pei; Jiang, Pengfei; Tan, Kang; Yu, Yunfeng; Qin, Genyan; Liu, Tingting; Tian, Sainan; Peng, Jun; Peng, Qinghua (Frontiers in Immunology, 2024)
Background: Linarine is a natural chemical component widely found in Buddleja officinalis Maxim., Chrysanthemum indicum L., Mentha canadensis L., and other medicinal plants. Modern pharmacological studies have shown that linarine with good anti-inflammatory and antioxidant activities can inhibit the proliferation and induce apoptosis of many kinds of tumor cells. Moreover, linarine showed protective effect on the liver, kidneys, and other organs. Methods: Inflammation model of human corneal epithelial cell (HCEC) was constructed using NaCl induction, and cytotoxicity was detected by the CCK8 assay. The levels of inflammatory factors tumor necrosis factor-α (TNF-α) and interleukin 1β (IL-1β) were measured using Enzyme-linked immunoassay (ELISA). Chronic painful stimulation (tail clamping) in combination with Benzalkonium Chloride Solution drops in a desiccator established a mouse model of dry eye disease (DED). The following parameters were recorded : body mass, anal temperature, tear secretion, tear film rupture time, and corneal fluorescein staining. The levels of inflammatory factors mitogen activated protein kinase (MAPK), nuclear factor kappa-B (NF-kB), c-Jun N-terminal kinase (JNK), IL-1β, Interleukin 18(IL-18), A2A, A3, P2X4, P2X7, P2Y1 were measured by using immunofluorescence (IF) staining. Results: Linarine can inhibit the secreation of TNF-α, and IL-1β in HCECs. Linarine prolonged tear film rupture time, promoted tear secretion, repaired corneal damage, and reduced the levels of inflammatory factors of MAPK, NF-kB, JNK, IL-1β, IL-18, and modulated the levels of the purinergic receptor. Conclusions: Linarine is effective in treating dry eye in mice by inhibiting purinergic receptors-meidated inflammatory response. [keywords] dry eye disease (DED) ； linarine ； purinergic receptors; inflammatory responses; cornea Scheme 1. Linarine's applicability in therapy for DED mice.